(untitled) (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Ramona Y, Darmayasa IBG, Line MA. 2022. Biological control of Sclerotinia minor attack on pyrethrum plants by Trichoderma harzianum in glasshouse experiment. Biodiversitas 23: 3264-3269. The aim of this research was to elucidate the efficacy of Trichoderma harzianum (isolate Td22) grown in a ratio of 2:8 millet seeds and wood fiber waste (WFW) compost mixture to suppress Sclerotinia minor infection in pot trails on the pyrethrum plants (in 0.5 L pots). The pots were filled with soil and mixed with Td22-grown WFW compost to obtain a concentration of 5% v/v. The S. minor (fungal pathogen) previously grown in millet seeds amounted at 2.0 g per pot, was then evenly inoculated at 2 cm below the surface of potting mix. Soil without compost amendment, amended with pathogen only, or without pathogen inoculation served as controls. All pots were acclimatized for 4 days in a shade house prior to transplanting (4 seedlings per pot) of pyrethrum seedlings (aged of 3 weeks). Eight replications per treatment were run for 8 weeks. The results showed that 5% v/v compost-grown Td22 provided 78% protection to pyrethrum plants at week 8. Each surviving plant in Td22-treated pots also showed significantly higher average dry weight (p<0.05) than those planted in S. minor control treatment, indicating that Td22 has a potential to be developed as a novel fungal antagonist or a plant growth-promoting fungus.